Development and DSP Implementation of Ann-Based VPWM in a Voltage Source Inverter - Martin Kuchar; Pavel Brandstetter (Communications - Scientific letters of the University of Zilina, 2004)
This paper deals with development, simulation and DSP implementation of space vector modulator based on artificial neural network. The modulator is designed for a voltage source inverter utilization. In the contribution an explanation of presented ANN-based VSI-VPWM is described. Main features and advantages of the used algorithm are summarized too. The entire AC electrical drive consists of a frequency converter, induction motor and microprocessor control system. In the paper a description of the control system with TMS 320C40 DSP is also given. A very important part of the development is simulation, because it is necessary to verify rightness of the algorithm. The entire drive was simulated in the program Matlab with Simulink toolbox.